Interactions between Seismic Safety and Energy Efficiency for Masonry Infill Walls: A Shift of the Paradigm - André Furtado; Hugo Rodrigues; António Arêde; Fernanda Rodrigues; Humberto Varum (Energies, 2022)
Currently, the upgrade of existing reinforced concrete (RC) buildings focuses only on energy retrofitting measures due to the current policies promoted in the scope of the European Green Deal. However, the structural deficiencies are not eliminated, leaving the building seriously unsafe despite the investment, particularly in seismic-prone regions. Moreover, the envelopes of existing RC buildings are responsible for their energy efficiency and seismic performance, but these two performance indicators are not usually correlated. They are frequently analyzed independently from each other. Based on this motivation, this research aimed to perform a holistic performance assessment of five different types of masonry infill walls (i.e., two non-strengthened walls, two walls with seismic strengthening, and one wall with energy strengthening). This performance assessment was performed in a three-step procedure: (i) energy performance assessment by analyzing the heat transfer coefficient of each wall type; (ii) seismic performance assessment by analyzing the out-of-plane seismic vulnerability; (iii) cost–benefit performance assessment. Therefore, a global analysis was performed, in which the different performance indicators (structural and energy) were evaluated. In addition, a state-of-the-art review regarding strengthening techniques (independent structural strengthening, independent energy strengthening, and combined structural plus energy strengthening) is provided. From this study, it was observed that the use of the external thermal insulation composite system reduced the heat transfer coefficient by about 77%. However, it reduced the wall strength capacity by about 9%. On the other hand, the use of textile-reinforced mortar improved the strength and deformation capacity by about 50% and 236%, but it did not sufficiently reduce the heat transfer coefficient. There is a need to combine both techniques to simultaneously improve the energy and structural energy performance parameters.